The Effectiveness of Digital Platform in Enhancing Students' Participation and Engagement in Learning English - Rizky Mulya Pratama; Sunarti (Universitas Islam Negeri Alauddin Makassar, 2024)
The COVID-19 pandemic has disrupted traditional teaching methods, causing students to struggle with engagement in English language learning. However, digital platforms have emerged as a creative solution to maintain participation and teamwork in virtual spaces. This study aims to evaluate the relationship between the duration of time students spend using English learning platforms and their engagement in online learning through digital platforms. The research uses a quantitative approach while the instruments used in this study include students' usage duration of the digital platform and their learning progress monitored within the platform's features. The sample of this research focuses on first-semester students enrolled in the General Basic English Course at private university in Samarinda. Based on a correlation analysis, it demonstrates a significant relationship between the duration of digital platform use and student progress in learning English. This suggest that the digital platform significantly affects students' participation and engagement in learning English. According to ANOVA, the result demonstrated significant differences between the group means. This suggest that the digital platform significantly affects students' participation and engagement in learning English. based on the multiple comparison between groups, the result showed significant differences among three groups regarding the effectiveness of a digital platform in enhancing student participation and engagement in learning English. These findings underscore the varying levels of effectiveness of the digital platform across different student groups, suggesting that these differences should be considered when implementing learning strategies. For the implication of this study, it is expected to contributes to the field of educational technology by offering insights into the impact of digital platforms on language learning engagement. Additionally, to informs educational policymakers, supporting evidence- based decisions on technology integration in language learning programs.